Indigenous Resistance and Environmental Ethics: A Socio-Ecological Re-reading of Guru Tegh Bahadur and Mahatma Gandhi - Daksh; Mohit Dahiya (The Bioscan, 2026)
Indigenous resistance has been studied extensively in connexion with political ecology and environmental studies and is mostly analysed within the framework of environmental ethics and modern industrialism criticism through the Gandhian thought.